Essential nmr for scientists and engineers - Blümich, Bernhard (Springer Berlin Heidelberg, 2005)
ESSENTIAL NMR is a set of lecture notes for scientists and engineers who want to brush up on their knowledge of NMR. This book is also a compendium for graduate and postgraduate students of physics and chemistry as well as for their teachers, covering all fields of NMR, i.e. NMR methodology and hardware, chemical analysis, 2D-spectroscopy, NMR imaging, flow NMR, and quality control NMR. The material, selected and organized for a one-semester course, is presented with pairs of pages addressing particular topics. One page of each pair provides a text containing the key information, the other page shows a color illustration. This is the most comprehensive textbook on NMR to date. The book is intended for beginning graduate students and doctoral students of Physics, Chemistry, Chemical Engineering, and Material Science. Basic principles - spectroscopy - Imaging and mass-transport - Low-field and unilateral nmr.